Constructions of multi-scale 3D digital rocks by associated image segmentation method - Wang, Haiyan; Yang, Xuefeng; Zhou, Cong; Yan, Jingxu; Yu, Jiaqi; Xie, Kui (Frontiers in Earth Science, 2025)
Digital rocks constructed from micro-CT image at a single-resolution face limitations in accurately identifying the entire pore space and mineral components of tight sandstones, due to their high content of nanoscale pores and clay. Consequently, the porosity values derived from such digital rocks are significantly lower compared to those obtained through laboratory measurements, resulting in discrepancies between the measured and calculated petrophysical properties. This study introduces a multi-scale digital rock modeling method by integrating three-dimensional micro-CT images acquired at two distinct resolutions and two-dimensional SEM images. Plunger-shaped core samples and their corresponding sub-samples were scanned at resolutions of 13.99 μm/voxel and 2.99 μm/voxel, respectively. The scale-invariant feature transform (SIFT) image registration technique was employed to accurately align the two sets of grayscale CT images. Correlation curves between the grayscale value in low-resolution CT images and various mineral contents were established based on the aligned regions, and utilized to construct multi-scale digital rock models. Intragranular pores, unresolvable by the micro-CT images, were identified using SEM imaging, enabling the incorporation of fine-scale features into the models. The resulting multi-scale digital rock models exhibited bulk porosity values that closely matched laboratory helium porosity measurements. Additionally, the elastic moduli calculated by the differential effective medium (DEM) model and the finite element method (FEM) demonstrated good correspondence with experimental results. These results validate the proposed multi-scale digital rock modeling method as an effective approach for accurately characterizing the porosity and mineral components of tight sandstone reservoirs.